Impacts of pre-transport fasting time on blood parameters, carcass characteristics and meat quality of Japanese quails - Lopes, Luana Kelly; Maciel, Mônica Patrícia; Silva, Fredson Vieira e; Oliveira, Laura Lúcia dos Santos; Souza, Luiz Felipe Martins (Semina: Ciências Agrárias, 2024)
The objective of this research was to evaluate the effects of different fasting times before transport to the slaughterhouse on blood parameters, carcass characteristics and meat quality of Japanese quails. In total, 300 Japanese quails were used, with an average age of 14 months (discard age) and an initial body weight of 185.3 Â± 7.3 g. The quails were distributed in a completely randomised design with six treatments and five replications of 10 birds each. The treatments consisted of different fasting periods on the farm: zero (control), 1 hour and 30 minutes, 3 hours, 4 hours and 30 minutes, 5 hours and 30 minutes and 7 hours. The quails showed higher blood glucose concentrations with increasing fasting time, but there was no increase in total proteins, albumin, lactate, creatine kinase, uric acid, globulin and the albumin/globulin ratio. The weight and yield of the hot carcass and the weight of the cold carcass decreased with increasing fasting time. Quails that fasted for 7 hours had lower hot carcass and cold carcass weights compared to quails that did not fast. There was no influence of fasting time on meat quality. A fasting period of 5 hours and 30 minutes before transportation is recommended to ensure proper emptying of the digestive tract and the maintenance of the carcass weight of Japanese quails.